Secrets of the Silent Witch. 1 - Isora, Matsuri (Yen Press, 2023)
Monica Everett is the Silent Witch, the only mage in the world who has mastered the art of unchanted magecraft. But Monica hides a secret: the reason she learned to use magic without speaking is merely because of her extreme shyness. Until now, she's been content living a peaceful life hidden away in the mountains, but an unexpected visit from a colleague brings her a task more daunting than any other. Now it's up to her to infiltrate an academy and protect the second prince from danger... without letting her fears get to her!" --